DOPING EFFECT FROM PT ATOM IN SILICON STRUCTURE AND TREATMENT BY ROENTGEN RADIATION FLASH EXPOSURE - Sangwaranatee, Narong; Srithanachai, Itsara; Niemcharoen, Surasak (My University, 2021)
In the present, semiconductor device has big change by using high technology to improve performance and push the limit of device to support with new product to support demand of human. One of the device we are still using in our life is power semiconductor, this can support many kind of work such as satellite, power electronics and automobile. The technique in this paper will focus by using the characteristics of Pt in silicon structure for high speed and treatment with flash Roentgen radiation exposure. In principle, Pt atom can generate trapping center in silicon structure and help for increase switching time for semiconductor base on silicon substrate. However, Pt has not only good property for device but still has damage in structure is generate cluster in silicon structure that make Pt atom not really help to improve performance completely. The another goal of this paper will using flash Roentgen radiation exposure help to treatment and destroy cluster from Pt atom in silicon structure.
Keywords: C-V characteristics; Power device; Pt atom; Roentgen radiation